Progressive Metaplastic and Dysplastic Changes in Mouse Pancreas Induced by Cyclooxygenase-2 Overexpression - Jennifer K.L. Colby (Neoplasia: An International Journal for Oncology Research, 2008)
Cyclooxygenase-2 (COX-2) overexpression is an established factor linking chronic inflammation with metaplastic and neoplastic change in various tissues. We generated transgenic mice (BK5.COX-2) in which elevation of COX-2 and its effectors trigger a metaplasia-dysplasia sequence in exocrine pancreas. Histologic evaluation revealed a chronic pancreatitis-like state characterized by acinar-to-ductal metaplasia and a well-vascularized fibroinflammatory stroma that develops by 3 months. By 6 to 8 months, strongly dysplastic features suggestive of pancreatic ductal adenocarcinoma emerge in the metaplastic ducts. Increased proliferation, cellular atypia, and loss of normal cell/tissue organization are typical features in transgenic pancreata. Alterations in biomarkers associated with human inflammatory and neoplastic pancreatic disease were detected using immunohistochemistry. The abnormal pancreatic phenotype can be completely prevented by maintaining mice on a diet containing celecoxib, a well-characterized COX-2 inhibitor. Despite the high degree of atypia, only limited evidence of invasion to adjacent tissues was observed, with no evidence of distant metastases. However, cell lines derived from spontaneous lesions are aggressively tumorigenic when injected into syngeneic or nude mice. The progressive nature of the metaplastic/dysplastic changes observed in this model make it a valuable tool for examining the transition from chronic inflammation to neoplasia.